Surface-exposed antigenic cleavage fragments of Neisseria gonorrhoeae proteins 1A and IB. - Schmitt, S (1986)
Whole bacteria, isolated outer membranes, and purified protein I (PI) from one transparent (O-) and two different opaque (O+) phenotype gonococcal strains (serogroups I, II, and III; PI serotypes 1, 5, and 9b) were each treated with tolylsulfonyl phenylalanyl chloromethyl ketone-trypsin, alpha-chymotrypsin, and proteinase K. Protein IA (PIA) of strain 7122 (O-, serotype 1, serogroup I) was resistant to proteolysis by tolysulfonyl phenylalanyl chloromethyl ketone-trypsin and alpha-chymotrypsin and only slightly affected by proteinase K, as long as it was associated with intact bacteria or isolated outer membranes. Purified PIA however was cleaved by these enzymes, resulting in two to five fragments. In contrast, all preparations of strains 5766 opaque phenotype (O+, serotype 7, serogroup II) and 1955 (O+, serotype 9b, serogroup III) were accessible to proteolysis, resulting in cleavage fragments of PIB compatible to those described previously by O. Barrera and J. Swanson (Infect. Immun. 44:565-568, 1984), M. S. Blake et al. (Infect. Immun. 33:212-222, 1981), and Blake (in G. K. Schoolnik, ed., The Pathogenic Neisseriae, 1985). Our data indicated that the purified PIB fraction was more accessible to proteases than the PIBs of whole bacteria or outer membranes. The fragmentation pattern of PIA cleavage products were quite different from PIB fragments, consistent with the different structure of these two groups of PI molecules. Time-dependent cleavage experiments with proteases, i.e., alpha-chymotrypsin, indicated that PIA was subsequently cleaved into smaller fragments. Highly reactive monoclonal antibodies, each specific for a surface-exposed epitope of PIA of strain 7122 or PIB of strains 5766 and 1955, as assessed by coagglutination, Western blot, and immunofluorescence, were reacted with PIA and PIB cleavage fragments in Western blot experiments. All cleavage fragments of the purified PIA and PIB preparations with molecular weights of greater than or equal to 14,200 showed immune reaction in Western blotting, whereas whole cell and outer membrane PIB fragments were less reactive with the specific monoclonal antibodies.